Meaning-making tools in intersemiotic translation (based on screen adaptation of “The hours”) - Tashchenko, Ganna (Cognition, Communication, Discourse, 2022)
The present article focuses on screen adaptations as intersemiotic translation which gives an opportunity to transpose written word into the multimodal space of cinema. Taking up the role of translators who act as mediators between different semiotic systems, film-makers face a range of challenges associated with the meaning-making resources available to the creator of a book and a film, respectively. They have to take into account a variety of factors ranging from the need to preserve the spirit of the book and its aesthetic value to the obligation to ensure commercial success of the film. However, reinterpretation of a literary work for screen purposes inevitably produces a new work of art which starts its own life in the cultural environment it is meant for. Unleashing their creativity, film-makers decide which elements of the book they consider essential to convey the key message of the writer and which could be sacrificed to provide for the visual appeal of the work of cinema. A vivid example of such a challenge is seen in filming “The Hours” based on the novel by M. Cunningham, a story of three women bound through time with a book. Virginia Woolf writing her “Mrs. Dalloway”, Laura Brown reading it and Clarissa Vaughn nicknamed Mrs. Dalloway by her former lover—all of them are struggling to find their true selves in the world, which dictates the way they must live their femininity. The battles they have to fight every single day without having the right to speak up are mostly represented in their internal monologues the novel abounds with. The film, in its turn, focuses on the main events in the story reinforcing them with powerful symbols such as the kiss that reveals true desires of Virginia and Laura while showing Clarissa that her life goes on; the cake that becomes an embodiment of Laura’s failure as a spouse and a mother; water that will swallow Virginia and become a point of no return for Laura, and flowers presaging death for Virginia but fortelling life for Clarissa. An intricate mixture of music, image, and unrivaled play of actors produce a coherent and eloquent narrative, which makes viewers rethink gender stereotypes as well as Virginia Woolf’s legacy.